Two-dimensional spreading properties and sealing characteristics of fluorocarbon surfactants on several typical hydrocarbon fuels - Xuhong Jia (Nature Portfolio, 2021)
Abstract A new method for studying the two-dimensional spreading properties and sealing characteristics of surfactant solution on oil surface was provided. The actual spreading situation of the C4-Br/oil systems in axisymmetric geometry was observed directly using HD camera for the first time and the results showed that the aqueous film expanded outwards in a circle with the guiding device as the center. Meanwhile, the relation between spreading radius and time was investigated and evaluated using the model for surface-tension-viscous regime. The root-mean-square deviation (RMSD) values obtained from the correlation for all of the systems we studied below 1.64, indicating a good agreement between the experimental and theoretical values. The results of sealing experiments showed that the aqueous film could absolutely seal the oil surface for 27–65 s and the sealing effect would be lost after 216–742 s for different systems. The stronger the volatility was, the shorter the sealing time was. Additionally, the volume percentage of oil vapor with film was always lower than that without film even when the evaporation was saturated. These findings were of great significance to guide the preparation of efficient AFFF.